Experimental and numerical analysis of PMMA impact fracture. (September 2020) - Kazarinov, N.A.; Bratov, V.A.; Morozov, N.F.; Petrov, Y.V.; Balandin, V.V.; Iqbal, M.A.; Gupta, N.K.
Highlights: Penetration of PMMA plates was studied experimentally and numerically. Incubation time fracture model was used for the fracture simulations. Plates with different thicknesses were studied. Residual and threshold impactor velocities were investigated. Abstract: The work presents experimental and numerical results on dynamic fracture of PMMA plates subjected to impact loading. The experimental tests were conducted using steel cylinder-shaped projectile accelerated using a gas gun. In order to evaluate performance of the tested specimens, residual impactor velocity was assessed using high-speed photography setup. Square-shaped PMMA specimens with three thicknesses were investigated using various projectile velocities. For all the three specimen types the ballistic limits were experimentally obtained. The conducted experiments were numerically simulated using finite element method with explicit time integration scheme and incubation time fracture model for the material failure prediction. Experiments with all three specimen configurations were successfully simulated using one parameter – incubation time, which was evaluated from existing experimental data on the dynamic fracture of PMMA. In addition to the simulations of the real experiments estimates on performance of a sample with a virtual geometry were made using the developed numerical approach.